2003
DOI: 10.4141/p02-012
|View full text |Cite
|
Sign up to set email alerts
|

Optimum plant population density for chickpea and dry pea in a semiarid environment

Abstract: . 2003. Optimum plant population density for chickpea and dry pea in a semiarid environment. Can. J. Plant Sci. 83: 1-9. Chickpea (Cicer arietinum L.), an annual grain legume, is being broadly included in cereal-based cropping systems throughout the semiarid Canadian prairies, but information on optimum plant population density (PPD) has not been developed for this region. This study, which was conducted from 1998 to 2000 in southwestern Saskatchewan, determined the effect of PPD on field emergence, seed yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 8 publications
(7 reference statements)
10
65
0
1
Order By: Relevance
“…The overall effects of PPD on chickpea seed yield have been reported elsewhere (Gan et al 2003). In brief, seed yield increased linearly with increasing PPD when chickpea was grown on CS.…”
Section: Seed Yieldmentioning
confidence: 97%
See 3 more Smart Citations
“…The overall effects of PPD on chickpea seed yield have been reported elsewhere (Gan et al 2003). In brief, seed yield increased linearly with increasing PPD when chickpea was grown on CS.…”
Section: Seed Yieldmentioning
confidence: 97%
“…In a previous study, Gan et al (2003) reported that desi chickpea increased fertile pods m -2 by 28% as plant population density increased from 20 to 50 plants m -2 , whereas this level of PPD changes increased pods m -2 by 10% for a large-seeded kabuli crop. On average, kabuli plants produced 45 to 50% as many pods m -2 as desi plants under normal growing conditions.…”
Section: Pod Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of seeding densities on yield was minimal. Sugar snap, like the seed peas mg g -1 , has considerable capacity to adapt, with the ability to reach yield levels that are near-optimal with planting densities as wide-ranging as 75 and 150 plants m -2 (Gan et al, 2003;Tawaha and Turk 2004;Pageau et al, 2007). However, the effect was not the same every year.…”
Section: Discussionmentioning
confidence: 99%